Productivity and global warming potential of direct seeding and transplanting in double‐season rice of central China. Issue 1 (31st August 2022) - Xu, Le; Yuan, Shen; Wang, Xinyu; Yang, Guodong; Xiangcheng, Pan; Yu, Xing; Wang, Fei; Huang, Jianliang; Peng, Shaobing
Abstract: Labor and water scarcity requires crop establishment of double‐season rice to be shifted from traditional transplanting to direct seeding. Owing to the limited thermal time, only ultrashort‐duration cultivars of about 95 d can be used for direct‐seeded, double‐season rice (DDR) in central China. However, whether the shift in crop establishment of double‐season rice can reduce greenhouse gas emissions without yield penalty remains unclear. Field experiments were conducted in Hubei province, central China with three treatments of crop establishment in the early and late seasons of 2017 and 2018. Treatments included DDR with ultrashort‐duration cultivars (DDRU ), transplanted double‐season rice with ultrashort‐duration cultivars (TDRU ), or with widely grown cultivars which have short duration of about 110 d (TDRS ). It was found that crop growth duration of DDRU was 6–20 days shorter than that of TDRU and TDRS, respectively. Ultrashort‐duration cultivars under DDRU achieved 15.1 t ha −1 of annual yield that was 9.4% higher than TDRU, and only 3.2% lower than TDRS . DDRU reduced the annual cumulative CH4 emission by 32.0–46.1%, but had no difference in N2 O emission in comparison with TDRU and TDRS . The highest CO2 emission was TDRS followed by DDRU, and then TDRU . As a result, shifting from TDRU and TDRS to DDRU decreased global warming potential and yield‐scaled greenhouse gas intensity by 28.9–53.2% and 20.7–63.8%, respectively. These findings suggest that DDR can be a promising alternative to labor‐ and water‐intensive TDR in central China that offers important advantages in mitigating agricultural greenhouse gas emissions without sacrificing grain yield. Abstract : Direct‐seeded, double‐season rice (DDR) using ultrashort‐duration cultivars achieved 15.1 t ha‐1 of annual yield within 188 days.Yield performance of DDR was comparable to that of transplanted double‐season rice (TDR).Shifting from DDR to TDR significantly reduced GWP and GHG intensity by 28.9‐53.2% and 20.7‐63.8%, respectively.